A Strategy for IMF Engagement on Social Spending. (Policy Papers; Policy Paper ;, 2019)
Interest in social spending issues has intensified over the last decade. This reflects concerns about rising inequality and the need to support vulnerable groups, especially in the aftermath of the global financial crisis. In line with this, the Fund has also increased its engagement on social spending issues. This paper outlines a strategy to guide IMF engagement on social spending issues going forward.